PENGEMBANGAN KARTU DOMINO BAHASA JAWA KRAMA INGGIL PADA MATERI UNGGAH-UNGGUH DI KELAS V MI - Mariana, Ilvi; Bahrodin, Ariga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The decline in the use of Jawa Krama Inggil at the elementary school level has become a serious issue in efforts to preserve culture and shape polite student character. This condition is caused by several factors, such as a lack of student interest, limited instructional time, and a shortage of engaging learning media. This research aims to develop learning media in the form of Jawa Krama Inggil Domino Cards and to analyze the feasibility and attractiveness of this media for fifth-grade students at MI Al-As`ad Diwek Jombang. The method used in this study is the Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data collection was conducted through observation, interviews, questionnaires, and documentation. The developed media was validated by material experts, media experts, and Javanese language teachers, and was subsequently tested in small and large group trials. The results of the study indicate that the Jawa Krama Inggil Domino Cards received a "highly feasible" rating, with percentages of 94% from material experts, 94% from media experts, and 92% from teachers. Student responses showed a very high level of interest, reaching 94% in small group trials and 96.56% in large group trials. Consequently, this media is declared appropriate, engaging, and effective in improving students understanding, learning motivation, and Krama Inggil language skills while supporting the preservation of local culture.